Regulation of Glyoxysomal Enzymes during Germination of Cucumber: 3. IN VITRO TRANSLATION AND CHARACTERIZATION OF FOUR GLYOXYSOMAL ENZYMES - Riezman, Howard (1980)
Monospecific antibodies raised against four glyoxysomal enzymes (isocitrate lyase, catalase, malate synthase, and malate dehydrogenase) have been used to detect these proteins among the products of in vitro translation in a wheat germ system programmed with cotyledonary RNA from cucumber seedlings. In vitro immunoprecipitates were compared electrophoretically with the same enzymes labeled in vivo and also with the purified proteins. Isocitrate lyase yields two bands on sodium dodecyl sulfate-polyacrylamide gels, as synthesized both in vitro (61.5K and 60K products) and in vivo (63K and 61.5K polypeptides). Both the 63K and 61.5K subunits can also be demonstrated for the isolated enzyme. The two subunits are antigenically cross-reactive and yield similar electrophoretic profiles upon partial proteolytic digestion. A larger subunit is seen in vitro than in vivo for both malate dehydrogenase (38K versus 33K) and catalase (55K versus 54K); this suggests a need for processing which is often a characteristic of proteins that must be transported across or into membranes. Malate synthase has a molecular weight of 57K both in vitro and in vivo, but the isolated enzyme is a glycoprotein, containing N-acetyl glucosamine, mannose, and possibly also fucose and xylose. This indicates that the polypeptide portion of the isolated enzyme is smaller than the in vitro product and suggests processing of malate synthase also. None of the other three enzymes appears to be glycosylated. The implications of these size differences for the compartmentalization of matrix and membrane-bound glyoxysomal enzymes are discussed.